A systematic review of sacral nerve stimulation for low anterior resection syndrome. (September 2015) - Ramage, L.; Qiu, S.; Kontovounisios, C.; Tekkis, P.; Rasheed, S.; Tan, E.
Abstract Aim The efficacy of sacral nerve stimulation (SNS) in low anterior resection syndrome (LARS) is largely undocumented. A review of the literature was carried out to study this question. Method Pubmed, Medline and Cochrane databases were searched for relevant articles up to August 2014. Studies were included if they evaluated the use of SNS following rectal resection and assessed at least one of the following end‐points: bowel function, quality of life and ano‐neorectal physiology. No restrictions on language or study size were made. Results Seven papers were identified including one case report and six prospective case series. These included 43 patients with a median follow‐up of 15 months. After peripheral nerve evaluation definitive implantation was carried out in 34 (79.1%) patients. Overall, 32 (94.1%) of the 34 patients experienced improvement of symptoms which, based on intention to treat, was 32/43 (74.4%). Conclusion The review suggests that SNS for faecal incontinence in LARS has success rates comparable to its use for other forms of faecal incontinence.